Function and therapeutic potential of transient receptor potential ankyrin 1 in fibrosis - Wei, Yicheng; Cai, Jialuo; Zhu, Ruiqiu; Xu, Ke; Li, Hongchang; Li, Jianxin (Frontiers in Pharmacology, 2022)
The transient receptor potential (TRP) protein superfamily is a special group of cation channels expressed in different cell types and signaling pathways. In this review, we focus on TRPA1 (transient receptor potential ankyrin 1), an ion channel in this family that exists in the cell membrane and shows a different function from other TRP channels. TRPA1 usually has a special activation effect that can induce cation ions, especially calcium ions, to flow into activated cells. In this paper, we review the role of TRPA1 in fibroblasts. To clarify the relationship between fibroblasts and TRPA1, we have also paid special attention to the interactions between TRPA1 and inflammatory factors leading to fibroblast activation. TRPA1 has different functions in the fibrosis process in different organs, and there have also been interesting discussions of the mechanism of TRPA1 in fibroblasts. Therefore, this review aims to describe the function of TRP channels in controlling fibrosis through fibroblasts in different organ inflammatory and immune-mediated diseases. We attempt to prove that TRPA1 is a target for fibrosis. In fact, some clinical trials have already proven that TRPA1 is a potential adjuvant therapy for treating fibrosis.